Perspectives of Care Experienced Young People Regarding Their Academic Experiences in Further Education - Howard, Kirstie; MacQuarrie, Sarah (Frontiers in Education, 2022)
Background The academic attainment of care experienced young people (CEYP) is consistently reported as below the national average. Studies emphasize associations between low academic attainment and poor life outcomes. Most research relating to CEYP and education, has highlighted the impact of educational barriers and opportunities on their progression and subsequent attainment. Although, this research is almost exclusively concerned with schooling up to aged 16. Few studies have explored the perspectives and experiences of CEYP in further education, especially in a Scottish context. Aim This study aimed to centralize the views of CEYP to gain insight into the perceived achievement opportunities and barriers in FE. Secondly, this study aimed to consider CEYP experiences in FE to inform support services for CEYP. Sample Ten CEYP, aged 16–24, studying at a further education college in Scotland participated in the study. Seven further education colleges from geographically diverse regions are represented. Methods CEYP participated in semi-structured interviews to share their experience of further education. Findings Thematic analysis was used to produce the following main themes: Care experience and personal narratives, valuing further education and navigating support systems. Conclusion These findings provide unique insight into CEYP experiences of FE. Opportunities for CEYP achievement in FE included stability of education and accommodation, personalized and financial support and supportive relationships. Reported barriers included care-related challenges, additional support needs (ASN), staff knowledge and labeling practices. Priorities for support service development included increased CEYP informed and led services such as peer mentoring, corporate parenting training and peer education. Implications for FE practice and future research are discussed. A summary of key points for consideration are provided in the Supplementary Material and may be of particular interest to any educational organisation in a corporate parenting role.